Product Development of Jelly from Pineapple Juice by Community Enterprise, Ban Nong Pu Lok Women's Role Development Group, Mueang District, Prachuap Khiri Khan Province - Kanjana Punoiam, Weerawan Pinchumpholsang, Adhisiddhi Nujnetra, Chatchawal Sangthongluan and Bundit Anuyahong, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objectives of this study were 1) to develop 4 formulas of jelly from pineapple juice, consisting of pineapple juice jelly; aloe vera in pineapple juice jelly; dragon fruit in pineapple juice jelly; and jackfruit in pineapple juice jelly; 2) to design and develop packaging suitable for 4 formulas of pineapple juice jelly products; 3) to test the market and study the level of consumer acceptance towards 4 formulas of pineapple juice jelly products; 4) to take the lessons from the textbook on the development of jelly products from 4 formulas of pineapple juice; and5) to transfer technology to communities that are target groups such as community enterprises and communities in Prachuap Khiri Khan Province. Both qualitative and quantitative methodologies were employed as follows: 1) An evaluation form for jelly products from 4 prototypes of pineapple juice by 3 experts. Experts from Community Enterprise Group, Ban Nong Pulok Women's Role Development Group; 2) Market testing and acceptance assessment form for 4 formulas of jelly products from pineapple juice by 50 food and beverage business operators in Prachuap Khiri Khan Province; 3) Questionnaire surveyed the introduction of the prototype pineapple juice jelly product development manual to transfer knowledge to the community. The IOC value with a sample of 30 people and testing the confidence value was more than 0.7, 4) Evaluation form for the transcription of textbooks on the development of jelly products from pineapple juice; 5) Evaluation form for technology transfer to the community.